Tackling Community Challenges in the IMT-GT Region: A Multidisciplinary Strategy for Empowering Local Voices Songkhla, Thailand - Fathiah; Ferdi Nazirun Sijabat; Eliana; Suhelayanti; Mursyidin; Lasri (JKA, 2024)
Empowering communities is key to strengthening local participation and voice, especially in areas facing socio-economic challenges. The purpose of this community dedication activity is to explore a multidisciplinary strategy in empowering communities in Songkhla, Thailand, which is part of the IMT-GT region. Through a qualitative approach, the study analyzes the challenges faced by communities at Songkhlas and identifies various effective empowerment strategies. The results show that its main challenges include the lack of natural resource protection, limited community capacity, and weak coordination among stakeholders. The recommended empowerment strategies include strengthening community capacities through training and support, enhanced partnership and coordination between stakeholder, and the protection of natural resources through environmentally-conscious policies. The findings in this activity highlight the importance of a multidimensional approach in empowering communities in border regions, by involving various stakeholders to inclusive and equitable development